Audit Negara dalam Perspektif Maqāṣid al-Sharī‘Ah: Studi atas Perkara Korupsi Pembangunan Gereja Kingmi dan Pengadaan Lahan Munjul - Narayana, Raden Abyan Aradea; Machmud, Aris (STAINI Press, 2025)
The management and accountability of state finances is a fundamental aspect in realizing a fair and trustworthy government, as affirmed in the principles of maqāṣid al-sharī'ah, especially ḥifẓ al-māl (protection of property). In the practice of corruption criminal justice in Indonesia, the Audit Board (BPK) and the Financial and Development Supervisory Agency (BPKP) are two institutions that are often used as a reference in determining state losses. This article analyzes the dualism of authority between BPK and BPKP in two cases: the construction project of the Kingmi Mile 32 Church in Mimika (Case Number 03/Pid.Sus-KPK/2024/PN.Jkt.Pst) and the procurement of Munjul land by Perumda Pembangunan Sarana Jaya (Case Number 7092 K/Pid.Sus/2022 Jo. 20/Pid.Sus-TPK/2022/PT DKI). This study uses a qualitative method with a normative juridical approach, and integrates Gustav Radbruch's theory of legal certainty with the principles of maqāṣid al-sharī'ah. The results of the study show that the existence of two audit institutions with overlapping authorities causes legal uncertainty that can affect the objectivity of judges. From the perspective of maqāṣid al-sharī'ah, this situation threatens the achievement of justice and protection of public property. Therefore, regulatory and ethical affirmation is needed so that the state audit mechanism is in line with the principles of transparency, substantive justice, and protection of the public interest within the framework of Islamic law.